2017
DOI: 10.15835/nbha45210971
|View full text |Cite
|
Sign up to set email alerts
|

Floristic Change at the Drought Limit of European Beech (Fagus sylvatica L.) to Downy Oak (Quercus pubescens) Forest in the Temperate Climate of Central Europe

Abstract: An increase in drought could cause shifts in species composition and vegetation structure. In forests it limits the occurrence of drought sensitive tree species which become replaced by drought tolerant tree species and forest communities. Under temperate macroclimatic conditions, European beech (Fagus sylvatica L.) naturally dominates the forested landscape, except on extremely shallow soil in combination with high irradiation. On these sites beech reaches its drought limit, and is replaced by forests dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In spite of the shift in elevation, it seems unlikely that European beech in Serbia will migrate above current upper distribution limit at elevations exceeding 1,400 m during 2071–2100. This limitation of shifting can be attributed to the sensitivity of beech to drought and temperature rise (Kolář et al, 2017) as well as to shallow mountain soils with a low water storage capacity, which are usually present at higher elevations (Reif et al, 2017). The results obtained in the present study are consistent with the results of Seynave et al (2008) and Calvaruso et al (2017), who reported that beech growth is reduced by unfavorable soil properties, especially in shallow soils.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the shift in elevation, it seems unlikely that European beech in Serbia will migrate above current upper distribution limit at elevations exceeding 1,400 m during 2071–2100. This limitation of shifting can be attributed to the sensitivity of beech to drought and temperature rise (Kolář et al, 2017) as well as to shallow mountain soils with a low water storage capacity, which are usually present at higher elevations (Reif et al, 2017). The results obtained in the present study are consistent with the results of Seynave et al (2008) and Calvaruso et al (2017), who reported that beech growth is reduced by unfavorable soil properties, especially in shallow soils.…”
Section: Discussionmentioning
confidence: 99%
“…The sessile oak forests in the Coastal Ranges have experienced an increase in the relative richness for Mediterranean plants, but a decrease for Euro-Siberian plants. This is probably due to the warming conditions that have been occurring since 1950 (Martín Vide et al, 2016) which, as a result from an increase in hydric stress, promote the thermophilization of the community which, in turn, promotes plants sensitive to the new conditions being substituted for those more tolerant to them (Reif et al, 2017). On the NE Iberia Peninsula, these tolerant plants are the Mediterranean species which have adapted to the summer droughts in these climatic regions.…”
Section: Thermophilizationmentioning
confidence: 99%
“…Climate change impacts have also percolated into species distributions, with already documented northward shifts (Walther, 2003;Berger et al, 2007;Lenoir, 2008) and migrations toward higher elevations (Grabherr et al, 1994;Pauli et al, 1996Pauli et al, , 2003Walther et al, 2005). This has rendered changes in species composition (Reif et al, 2017) ultimately resulting in novel communities (Williams and Jackson, 2007;Bertrand et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In order to finish the model, digital spatial databases have been created for a number of 14 factors (Table 1) considered being representative for the expansion of the downy oak habitat. They have also been included in the ecological file (Stănescu, 1979;Reif et al, 2017).…”
Section: Creation Of Digital Spatial Databasesmentioning
confidence: 99%